Enhancing rice and wheat production by bridging yield gap in western Uttar Pradesh of India - Singh, Surendra; Singh, Ram Kumar; Singh, Randhir (Journal of Cereal Research, 2013)
Food security of India depends on rice and wheat crops. The study was conducted in Agra region of western Uttar Pradesh to assess yield gap at farmers’ field. Etah district was purposively selected because of large area under the rice-wheat crop system.  Out of the 15 blocks in Etah, Sakeet was selected having 176 villages of which 10 villages with maximum area under rice-wheat system were selected.  From the selected villages, 120 farmers were selected through proportionate random sampling from small (up to 2.00 hectares), medium (above 2.00–4.00 hectares) and large (more than 4.00 hectares) farmers. There is a yield gap on all the farms. The yield gap-II was more than the yield gap-I. The major constraints responsible for yield gap were late sowing/transplanting, higher prices of seed, non-availability of fertilizer at sowing time, lack of funds with farmers and infestation of pest and disease. There is further scope to increase productivity on the farms by managing the constraints. Providing quality inputs to the farmers at right time in sufficient quantity can help in reducing yield gap.